Foreign Direct Investment and Technology Licensing in a Polluting Industry - Jiyun Cao; Arijit Mukherjee (Environmental and Resource Economics, 2024)
Abstract We consider a firm's incentive for foreign direct investment (FDI) and international technology licensing in a polluting industry. We explain the rationale and the welfare implications of complementarity between FDI and licensing, i.e., the firm's strategy of “FDI and licensing” ( FL ), which is empirically relevant but ignored in the literature. When the environmental tax cannot be committed, the firm adopts the licensing strategy if the pollution intensity is not high, and the licensing strategy may create lower consumer surplus and welfare compared to both FDI and FL . However, if the pollution intensity is high, the firm undertakes FL , which provide higher consumer surplus and welfare compared to both licensing and FDI. When the government can commit to the environmental tax, the firm always prefers FL . The host-country welfare is higher but the consumer surplus and world welfare may be lower under the committed tax policy compared to the non-committed tax policy. These results hold under Cournot competition and Stackelberg competition. We further show that FL can be the equilibrium strategy of the foreign firm if there is fixed-fee licensing instead of a two-part tariff licensing, which is considered in the main analysis.
Additional information: F18;F23;L13;L24;Q56;Q58
Keywords: 330; Emission fee; Foreign direct investment; Technology licensing; Welfare